Methane recovery from marine gas hydrates: a bench scale study in presence of low dosage benign additives - Bhattacharjee, Gaurav; Choudhary, Nilesh; Barmecha, Vivek; Kushwaha, Omkar S.; Pande, Nawal K.; Chugh, Parivesh; Roy, Sudip; Kumar, Rajnish (Applied Energy, 2019)
De-pressurization is one approach which has been found to be economically feasible for methane recovery from marine hydrates. Hydrate dissociation being an endothermic process suggests that de-pressurization alone would not be sufficient and some additional stimulation would be required for sustained production from one such reservoir. Thermal stimulation may overcome the challenge posed by the endothermic dissociation process; however, economically it may not be ideal. A possible way out is to use thermal stimulation, but at relatively low temperatures as compared to conventional practice. This would be economical and can be accomplished in the presence of small doses of additives mixed in with the water stream used for thermal stimulation. In the present study, a number of benign additives were identified which when used in low concentrations enhance the kinetics of methane hydrate dissociation compared to pure water. Additives were first shortlisted from a wide potential pool using quantum mechanical calculations. These additives were later tested for their efficacy in stirred tank reactor to quickly identify the best additives for the job and few selected additives were then studied in a larger bench scale setup (fixed bed configuration) where they were injected in the form of an additive-water stream to dissociate already formed hydrates. Factors such as toxicity of the additive, fluidity of additive-water stream, foam formation on mixing of additive with water, etc. were also taken into account. An energy and efficiency analysis revealed that reported additives enhance the energy ratio and thermal efficiency of the process as compared to pure water stimulation.
Keywords: Bench scale; kinetics; Marine hydrate; methane hydrate; Methane recovery; Natural gas hydrate; Process

Molecular dynamics study on growth of carbon dioxide and methane hydrate from a seed crystal - Nakate, Prajakta; Ghosh, Bappa; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Chinese Journal of Chemical Engineering, 2019)
In the current work, molecular dynamics simulation is employed to understand the intrinsic growth of carbon dioxide and methane hydrate starting from a seed crystal of methane and carbon dioxide respectively. This comparison was carried out because it has relevance to the recovery of methane gas from natural gas hydrate reservoirs by simultaneously sequestering a greenhouse gas like CO2. The seed crystal of carbon dioxide and methane hydrate was allowed to grow from a super-saturated mixture of carbon dioxide or methane molecules in water respectively. Two different concentrations (1:6 and 1:8.5) of CO2/CH4 molecules per water molecule were chosen based on gas-water composition in hydrate phase. The molecular level growth as a function of time was investigated by all atomistic molecular dynamics simulation under suitable temperature and pressure range which was well above the hydrate stability zone to ensure significantly faster growth kinetics. The concentration of CO2 molecules in water played a significant role in growth kinetics, and it was observed that maximizing the CO2 concentration in the aqueous phase may not result in faster growth of CO2 hydrate. On the contrary, methane hydrate growth was independent of methane molecule concentration in the aqueous phase. We have validated our results by performing experimental work on carbon dioxide hydrate where it was seen that under conditions appropriate for liquid CO2, the growth for carbon dioxide hydrate was very slow in the beginning. (C) 2019 The Chemical Industry and Engineering Society of China, and Chemical Industry Press Co., Ltd. All rights reserved.
Keywords: Cage dynamics; CH4 recovery; CO2 sequestration; F-4 order parameter; kinetics; Natural gas hydrate; Thermodynamics